Status of Mental Health Amongst Undergraduate Students in Kenyan Universities (Qualitative Analysis of Sampled Studies) - Anika, Alice A.; Kwena, Jacinter A.; Lambert, Edward; Level, Rene T.; Islam, Mohammad Shahidul (European Journal of Applied Sciences, 2025)
Studies investigating mental health issues amongst university students have shown that mental distress in students is a driver of negative consequences, including suicidal thoughts, substance use, depression, anxiety disorders, poor cognitive functioning, and poor academic performance. The findings imply a similar mental health index in Kenyan universities, with respect to findings that mental health issues are more profound therein owing to associated stressors in these environments. This paper provides an anchor point for an assessment of the situation thereof, in the form of a meta-analysis of seven studies evaluating mental health among university students in Kenya. It was guided by five objectives: to determine the common mental health issues cited in the studies, to document summarised mental health challenges faced by university students, to profile the mental health services sited, to determine the coping mechanism used by students to manage their mental health issues if any, and to establish research gaps identified from the studies reviewed on mental health in the period between 2021-2022. The review revealed that depression, anxiety, and stress are the most prevalent mental health issues, due to diverse challenges. Further, it emerged that student counselling is the instrument put in place to handle mental health issues although students often resort to their own mechanisms when dealing with mental health issues. The findings revealed various gaps for further research in mental health management in Kenyan universities, in the form of relative unawareness or misinformation about mental health issues among university students.